Assistance in Making Project Modules for Strengthening Pancasila Student Profile for Teachers of SD 2 Puyoh Kudus Regency - Latifah Nur Ahyani; Jayanti Putri Purwaningrungrum; Agung Prihandono (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The project of strengthening the profile of Pancasila students is a new flagship activity in the Merdeka curriculum. This project is a learning activity through various disciplines where students can observe and solve problems in the school environment or the surrounding environment. SD 2 Puyoh is one of the elementary schools in Kudus Regency that chose the independent school path to change in the implementation of the independent curriculum. Because it is not a driving school, SD 2 Puyoh does not receive special assistance by incentive from other agencies/parties. Schools have difficulties in making project modules to strengthen the profile of Pancasila students. Thus, special assistance is needed to create project modules so that project activities to strengthen the profile of Pancasila students can run smoothly according to the expected results. Thus, the general purpose of this service activity is to provide assistance for teachers at SD 2 Puyoh to design and create project modules to strengthen the profile of Pancasila students by the topics, themes, and dimensions determined by the school. The method chosen in service activities is in the form of lectures, discussions/questions answers, and assignments. The result of this service activity is that teachers at Sd 2 Puyoh can design and make project modules to strengthen the profile of Pancasila students by the themes, topics, and dimensions that have been determined as well as the characteristics of the school environment.